MILK CONSUMPTION AFFECTS THE EXPRESSION OF AMELOGENIN IN AMELOBLAST CELLS DURING AMELOGNESIS (IN VIVO ANALYSIS OF PREGNANT MICE) - Hutami, Islamy Rahma; Dewi, Rizqa Citra; Christiono, Sandy; Mujayanto, Rochman (Jurnal Medali, 2022)
Background: Tooth development during embryonic period is complex process that needs enough nutrition for the formation of healthy dental tissue. Amelogenin are proteins that are secreted by ameloblast in the secretory stage that are importants in the crystal formation and the regulation of email thickness. Milk consumption during pregnancy can increase the expression of amelogenin of ameloblas cell in the tooth development process. This research aims to determine the impact of milk during pregnancy against the expression of amelogenin protein of ameloblast cell in the amelogenesis.Method: This is a true experimental laboratories research using post test only control group design. A total of 12 pregnant female mice (Mus Musculus L.) are used and divided into 2 groups, control group (given sterile aquades) and treatment group (given pregnancy milk). The measurements of amelogenin expression are done in 18th day of pregnancy period. Data were analyzed using Independent sampel of T-test analysis.Result: The result of this study showed that the average amounts of amelogenin expression in the treatment group are lower than the control group. Independent sampel t-test showed that there are significant difference in the amount of amelogenin expression between the control and treatment group (P>0,05)Conclusion: The milk consumption during pregnancy influenced the amelogenin expression of ameloblast cell in the mice fetus’s amelogenesis.